Association of Cholesterol Efflux Capacity With Clinical Features of Metabolic Syndrome: Relevance to Atherosclerosis - Julie Gall; Eric Frisdal; Randa Bittar; Wilfried Le Goff; Eric Bruckert; Philippe Lesnik; Maryse Guerin; Philippe Giral (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The contribution of high‐density lipoprotein to cardiovascular benefit is closely linked to its role in the cellular cholesterol efflux process; however, various clinical and biochemical variables are known to modulate the overall cholesterol efflux process. The aim of this study was to evaluate the extent to which clinical and biological anomalies associated with the establishment of the metabolic syndrome modulate cholesterol efflux capacity and contribute to development of atherosclerosis. Methods and Results This study involved patients (n=1202) displaying atherogenic dyslipidemia in primary prevention who were referred to our prevention center. Among these patients, 25% presented at least 3 criteria of the metabolic syndrome, as defined by the National Cholesterol Education Program Adult Treatment Panel III. We measured the capacity of 40‐fold diluted serum to mediate cholesterol efflux from cholesterol‐loaded human THP‐1 macrophages. Cholesterol efflux capacity was reduced progressively by 4% to 11% (P<0.0001) as a function of the increasing number of coexisting criteria for the metabolic syndrome from 1 to 5. This observation was primarily related to reductions in scavenger receptor class B member 1 and ATP binding cassette subfamily G member 1–dependent efflux. Multivariate analyses indicate that serum efflux capacity was significantly associated with established metabolic syndrome (odds ratio 0.45; 95% CI 0.28–0.72; P=0.009) independent of age, low‐density lipoprotein cholesterol, status with regard to lipid‐lowering therapy, smoking status, and alcohol consumption. Conclusions Our study revealed that individual criteria of metabolic syndrome are closely related synergistically to cholesterol efflux capacity. In addition, established metabolic syndrome and cholesterol efflux capacity were independently associated with clinical features of atherosclerosis.